Auditory feedback effect on temporal patterns during self-pacing treadmill walking - Trevor V. Evans; Megan E. Reissman; Timothy Reissman; Mark Shelhamer; Ajit M. W. Chaudhari (PLoS ONE, 2025)
Self-pacing treadmills provide advantages for assessing locomotion such as having a controlled environment and ability to accurately collect prolonged data, but the variable sounds from the treadmill belt motors when changing speed could provide artificial sensory feedback to walkers that may influence their gait while on the self-pacing treadmill. We hypothesized that temporal measures of gait on a proportionally-controlled self-pacing treadmill would be significantly different between when sound is present vs removed. Participants (n = 31) walked under two different conditions for five-minute periods each on the self-pacing treadmill: one without headphones, and the other with noise-cancelling headphones playing brown noise to mask the treadmill motor sounds. Mixed effects models were used to assess the impact of condition on temporal gait patterns. A custom accelerometer-based algorithm was created to detect gait events while on the treadmill. Significant differences were found in the average values of swing time, step time, and gait speed between the treadmill conditions. These differences between the two treadmill conditions suggest that self-pacing treadmill walkers may utilize the variable belt motor sounds available to them. Given the potential incorporation of auditory feedback for motor planning when walking on the self-pacing treadmill, researchers should consider belt motor sounds as a potential factor that affects gait patterns.